Influence of Volatiles on Mass Wasting Processes on Vesta and Ceres. Issue 3 (19th March 2021) - Parekh, R.; Otto, K. A.; Jaumann, R.; Matz, K. D.; Roatsch, T.; Kersten, E.; Elgner, S.; Raymond, C.
Abstract: We have analyzed mass wasting features, their distribution and deposit geometry on the two largest main asteroid belt objects—protoplanet Vesta and dwarf planet Ceres—and compared their geomorphology and mobility. Both asteroids have similar surface accelerations, but different surface compositions. Based on our observations and previous studies, we categorized three distinct morphological mass wasting classes: slumps, slides, and flow‐like movements. We conclude that Ceres has abundant features of flow‐like mass movements. Further, sliding and flow‐like characteristics are identified in craters within mid‐latitudes which supports the possibility of the presence of water ice in the near subsurface of Ceres. Vesta predominantly shows characteristics of dry granular‐like slide features which are distributed homogenously across the surface. By plotting the ratio between fall height ( H ) and run‐out length ( L ) (effective coefficient of friction, H / L ) against the run‐out length and spreading width ( W ), we demonstrate that deposits on Vesta terminate on shorter distances, whereas on Ceres they travel longer distances. The deposit geometry and the similar surface gravity on both asteroids suggest that the material composition and volatile component have a significant effect on deposit emplacement. However, both bodies' mass movements have similar effective coefficients of friction, even though Vesta's regolith is comparatively dry, whereas Ceres is rich in water ice. This leads to the conclusion that volatile content alone cannot be responsible for low effective coefficients of friction, and that more than one geological process is needed to explain the mass motion behavior and morphology. Plain Language Summary: Landslides are one of the most studied geological events on planetary bodies. Many scientists have contributed to a diverse database of knowledge with the aim to better understand these processes. They have been observed for various environmental conditions and are affected by gravity and the physical and chemical composition of the hosting body. However, it is challenging to delineate which specific type or morphology of landslide is sensitive to which parameter. On airless asteroids Vesta and Ceres, landslides have been well preserved, allowing for in‐depth analysis using remote sensing data. Interestingly, Vesta and Ceres' substantially different surface compositions have a major effect on landslides, despite their similar gravity. In our study, we have examined and updated the landslide inventory on both bodies, and performed an analysis of deposit mobility which will further enhance our understanding related to the material conditions, their mobility, and surface evolution. Key Points: We classified and estimated the H / L of mass movements to investigate the mechanisms of deposition on Vesta and Ceres Vesta has dry, granular‐like slides as dominant mass wasting feature, whereas Ceres has abundant features of flow‐like mass movements The mass wasting deposit mobility is influenced by the material composition and volatile content on Vesta and Ceres